Structural assessment procedures for existing concrete bridges : Experiences from failure tests of the Kiruna Bridge - Bagge, Niklas (Luleå tekniska universitet, Byggkonstruktion och brand, 2017)
Assessing existing bridges is an important task in the sustainable management ofinfrastructure. In practice, structural bridge assessments are usually conducted usingtraditional and standardised methods, despite knowledge that these methods oftenprovide conservative estimates. In addition, more advanced methods are available, suchas nonlinear finite element (FE) analysis, that are used for research purposes and cansimulate the structural behaviour of bridges more accurately. Therefore, it would beuseful to develop practical and reliable procedures for refined assessments using theseadvanced techniques.Focusing on the ultimate load-carrying capacity of existing concrete bridges, this thesispresents a procedure for structural assessments. The fundamental idea is to improve theassessment successively, as necessary to predict bridges’ structural behaviour adequately.The procedure involves a multi-level assessment strategy with four levels of structuralanalysis, and an integrated framework for safety verification. At the initial level (Level 1)of the multi-level strategy, traditional standardised methods are used, no failures arecovered implicitly in the structural analysis and action effects are verified using localresistances calculated using analytical models. In the subsequent enhanced levels (Levels2 – 4), nonlinear FE analysis is used for stepwise integration of the verification of flexural,shear-related and anchorage failures into the structural analysis. The framework for safetyverifications includes partial safety factor (PSF), global resistance safety factor (GRSF) andfull probabilistic methods. Within each of these groups, verifications of desired safetymargins can be conducted with varying degrees of complexity.To demonstrate and evaluate the proposed structural assessment procedure, comparativestudies have been carried out, based on full-scale tests of a prestressed concrete bridge.This was the Kiruna Bridge, located in the northernmost city in Sweden, which was duefor demolition as part of a city ...